Implications Of International Law For Settlement Of Maritime Border Disputes - Ayumi Kartika Sari (SEAN Institute, 2024)
International law is a framework that regulates relations between countries in various aspects, including resolving maritime border disputes. Resolving maritime border disputes is becoming increasingly important considering the rich natural resources in maritime areas. This research explores the implications of international law for various methods of resolving maritime border disputes, such as arbitration, negotiation, and settlement through international institutions. This analysis also includes the impact of international court decisions on the resolution of maritime border disputes between the countries involved. Through a comparative legal approach and case studies, this research highlights the challenges and opportunities in applying international law in the context of resolving maritime border disputes, and offers recommendations for improving the effectiveness of existing dispute resolution mechanisms. By understanding the implications of international law in depth, countries can strengthen their cooperation and promote peace and justice in the resolution of maritime border disputes.